RHETORICAL APPEALS OF SMARTPHONES ADVERTISEMENTS ON BILLBOARDS - Dyta Deasy Angriani; Lince Sihombing; Didik Santoso (Universitas Negeri Medan, 2018)
This research deals with rhetorical appeals namely logical, emotional, & ethical appeal used in 10 smartphone advertisements from billboards such as Lenovo, Oppo, Evercoss, Advan, Samsung, iPhone, Asus, Vivo, Huawei, & i-Cherry. The analytical tool of this study is based on Ramage et al’s (2010) theory of rhetorical appeals. A qualitative research design is suitably used in this study to give in-depth description and result of analysis. The findings of the analysis about the rhetorical appeals in the smartphone advertisements are: 1) The rhetorical appeals that mostly used in the ten smartphone advertisements is logical appeal due to the total 67 characteristic strategies, whereas emotional appeals only used in 29 characteristic strategies, & ethical appeal which cannot be counted in numbers as it is about credibility which is something qualitative namely expertise, experience, & reputation; 2) The rhetorical appeals in the ten smartphone advertisements are actualized by including the characteristic strategies that tightly represented to each type of rhetorical appeals; 3) The reasons of the actualization of rhetorical appeals application in the smartphone advertisements are because logical appeal attempts to provide sufficient evidence from empirical sources and sound reasoning.Keywords: Advertisement; Language Style; Persuasive strategies; Rhetorical Appeals